The Fragments of Polybius Compared with those of Duris and Phylarchus - Hau, Lisa Irene (Histos, 2021)
This paper uses the ‘fragments’ of Polybius, i.e., the citations of Polybius found in other authors, as a test case for how to employ such fragments to gain an understanding of now lost works of Hellenistic historiography such as those of Duris and Phylarchus, who have often been denigrated as ‘tragic historians’. Firstly, it compares the distribution of cover-texts citing Polybius with those citing Duris and Phylarchus. Secondly, it compares the types of content of the fragments of Polybius contained in Athenaeus and Plutarch with the types of content of the fragments of Duris and Phylarchus in these same cover-texts. Thirdly, it examines the degree of faithfulness of Athenaeus and Plutarch to their Polybian source in those fragments that correspond to independently preserved parts of Polybius’ text. Finally, some thoughts are proposed on what the fragments of lost works of Hellenistic historiography can and cannot tell us about the original works.